THE EFFECT OF PERCEIVED PRICE AND QUALITY ON CONSUMER SATISFACTION OF MS GLOW COSMETIC PRODUCTS IN GENERATION Z: Pengaruh Persepsi Harga Dan Kualitas Terhadap Kepuasan Konsumen Produk Kosmetik Ms Glow Pada Generasi Z - Dwi Aprilia Seno Putri, Namira; Djamaludin, Moh. Djemdjem (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Consumer behavior changes have become increasingly apparent during the COVID-19 pandemic, where people shop online more frequently, particularly for cosmetic products. This situation has led companies to pay more attention to the price and quality of their products to ensure consumer satisfaction, even when shopping online. This study aims to analyze the influence of price perception and quality perception on the satisfaction of MS Glow consumers in Generation Z. This research uses a cross-sectional study design and a survey method using an online questionnaire tool, Google Forms. The respondents in this study were 318 people selected through purposive sampling using voluntary sampling techniques. The data obtained were processed using Microsoft Excel 2013 software, Statistical Package for Social Science (SPSS) 25.0, and LISREL 8.80. The data analysis included descriptive analysis, correlation tests, and Structural Equation Modeling (SEM) analysis. The relationship test results show that there is a relationship between the respondents' characteristic variables with price perception and quality perception but not with consumer satisfaction. The influence test results show a positive and significant influence of price perception and quality perception on consumer satisfaction, and price perception has a significant positive effect on quality perception.